Home-based exercise is associated with improved cardiac functional performance in patients after acute myocardial infarction. Issue 12 (December 2020) - Ma, Liqun; Xiong, Xiaowei; Yan, Lihui; Qu, Jie; Hujie, Gulibaha; Ma, Yunjuan; Ren, Jun; Ma, Jianxin
Objective: To evaluate the effects of home-based exercise and physical activity on cardiac functional performance in patients after acute myocardial infarction (MI) during the coronavirus disease 2019 (COVID-19) pandemic. Methods: This retrospective study enrolled patients that received treatment of acute ST-segment elevation MI between and were followed-up 6 months later. The patients were divided into physically active and inactive groups based on their levels of home exercise after hospital discharge. Results: A total of 78 patients were enrolled in the study: 32 were physically active and 46 were physically inactive. The baseline characteristics were comparable between the two groups. At the 6-month visit, left ventricular ejection fraction and six-minute walking test (6MWT) were significantly improved while the proportion of patients with a New York Heart Association (NYHA) functional III classification was decreased in the active patients, whereas these parameters were not significantly changed in the inactive patients. In addition, the 6MWT was greater while the proportion of patients with an NYHA III classification was lower in the active group than the inactive group at the 6-month visit. Conclusion: Maintaining physical activity at home was associated with improved cardiac functional performance in patients after acute MI during the COVID-19 pandemic.